Modified ethylene/α‐octene co‐polymer elastomer composites with sacrificial bonds crosslinking networks and their reinforced mechanical performance. Issue 3 (23rd January 2023) - Liu, Huameng; Lin, Ruijun; Huang, Zhiyi; Yin, Xingshan; Lin, Xiaofeng; Lin, Wenjing; Li, Yong; Gu, Yuxin; Yi, Guobin
Abstract: The low tensile strength of ethylene/α‐octene co‐polymer (POE) limits its application as high‐strength materials. In this study, 3‐amino‐1, 2, 4‐triazole (ATA) was grafted onto maleic anhydride functionalized POE (PM) by melt reaction to obtain side chains capable of forming hydrogen bonding and metal coordination bonding, and then ferric chloride hexahydrate and POE are blended with them to obtain composite materials with high strength and fracture energy. The introduction of iron‐based coordination bonding and hydrogen bonding double dynamic crosslinking network endow thermoplastic elastomers with excellent mechanical strength and high toughness. Fourier transform infrared spectroscopy, rheological tests, and X‐ray photoelectron spectroscopy reveal the existence of non‐covalent crosslinking networks. Based on the strengthening and toughening of non‐covalent dynamic crosslinking network, the tensile strength of the modified POE elastomer composites achieves 12.5 MPa along with the elongation at break of 3540%. In addition, the modified POE elastomer composites exhibit improved melt elasticity and thermal stability. Abstract : The introduction of iron‐based coordination bonding and hydrogen bonding double dynamic crosslinking network endow thermoplastic elastomers with excellent mechanical strength and high toughness. Fourier transform infrared spectroscopy, rheological tests, and X‐ray photoelectron spectroscopy reveal the existence and sacrificial characteristics of non‐covalent crosslinking networks.